Assuring Quality of Health Professions Education in the Context of Cultural Diversity - Prihatiningsih, Titi Savitri; Boelen, Charles (Springer, 2022)
Countries with wide power distance in socio-hierarchy and collectivistic culture are mainly developing countries. Some have huge and large population with unique geographic and social environment (i.e., rural and remote areas). From the ‘feasibility’ and practical point of view, this kind of context tends to apply the ‘quantitative’ evaluation system, using numbers and statistics; and minimally applying the qualitative self-assessment & reflection in the accreditation system. Assuring quality for health profession education institutions in this kind of context is facing a dilemma due to the large numbers of institutions and study programmes, which have considerable disparities. The central and the local political decision affect the choice of the quality assurance system. This chapter discusses the definition of quality and standards in health profession education, as well as various accreditation systems in developed and developing countries. Characteristics of health profession education with social accountability values are also discussed which might influence the definition of quality.